Prefrontal activation in response to a plantar contact task under open and closed eye conditions in patients with cerebral infarction - Yang, Zhi-Quan; Wei, Meng-Fan; Xi, Jia-Ning (Frontiers in Neuroscience, 2023)
Objective This study investigates the effect of a bilateral (paralyzed side, healthy side) plantar contact task on dorsolateral prefrontal activation in patients recovering from cerebral infarction under open and closed eye conditions. Methods We selected 10 patients with cerebral infarction, admitted to the neurorehabilitation center of Beijing Rehabilitation Hospital, affiliated with Capital Medical University, from January 2019 to July 2020, who met our established criteria. Under open-eye and closed-eye conditions, the paralyzed and healthy sides performed the plantar contact tasks separately. The dorsolateral prefrontal region was monitored simultaneously with functional near-infrared spectroscopy (fNIRS), and activation was analyzed according to the curve-type changes of oxyhemoglobin and deoxyhemoglobin changes in the dorsolateral prefrontal cortex with 560 near-infrared monitoring channels. Results After stratifying the data based on the eyes-open and eyes-closed conditions, some degree of heterogeneity was observed between the layers. Under the eyes-closed condition, the Pearson χ2 was 0.142, with a p value of 0.706, indicating no significant impact of the eyes-closed condition on the activation of the dorsolateral prefrontal cortex during the plantar task, whether performed on the paralyzed or the healthy side. In contrast, the Pearson χ2 value was 15.15 for the eyes-open condition, with a p value of 0.002. This suggests that carrying out the plantar task, either on the paralyzed or the healthy side, with eyes open significantly influenced the activation of the dorsolateral prefrontal cortex. Furthermore, activation of the dorsolateral prefrontal cortex was 1.55 times higher when the task was executed with the paralyzed side compared to the healthy side. This implies that the paralyzed side was more likely to activate the dorsolateral prefrontal lobe when performing the plantar contact task under eyes-open conditions. Conclusion Observations via fNIRS revealed that the plantar contact task elicited dorsolateral prefrontal cortex activation. Moreover, the activation effect was intensified when performed on the paralyzed side under eyes-open conditions. Therapeutic methods that leverage these findings—namely cognitive-motor therapies that promote the recovery of motor functions by activating cognitive control brain regions via perception (information construction)—may hold promise.